Rising China Confronts Maritime Southeast Asia - Desker, Barry (2016)
China’s rejection of the Permanent Court of Arbitration ruling on its expansive claim to the South China Sea has set itself up for confrontation with maritime states in Southeast Asia. It will also heighten tensions within ASEAN.